Contemporary Chaucer across the centuries - Trigg, Stephanie 1958-; Hickey, Helen M. 1949-; Hickey, Helen M. 1949- (Book collections on Project MUSE., 2018)
This unique and exciting collection, inspired by the scholarship of literary critic Stephanie Trigg, offers cutting-edge responses to the writings of Geoffrey Chaucer for the current critical moment. The chapters are linked by the organic and naturally occurring affinities that emerge from Trigg's ongoing legacy; containing diverse methodological approaches and themes, they engage with Chaucer through ecocriticism, medieval literary and historical criticism, and medievalism. The contributors, trailblazing international specialists in their respective fields, honour Trigg's distinctive and energetic mode of enquiry (the symptomatic long history) and intellectual contribution to the humanities. At the same time, their approaches exemplify shifting trends in Chaucer scholarship. Like Chaucer's pilgrims, these scholars speak to and alongside each other, but their essays are also attentive to 'hearing Chaucer speak' then, now and in the future.